2013
DOI: 10.4172/2161-105x.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Lung Cell Crosstalk in the Obesity-ARDS Paradox

Abstract: Obesity is an increasingly frequent condition associated with increased adipose, systemic and pulmonary inflammation. There is an emerging and unexpected finding that obese individuals may not be at a greater risk for ARDS and, indeed, may even be partially protected against ARDS. This finding is known as the Obesity-ARDS Paradox. In this review we discuss the observations regarding this intriguing phenomenon and begin to elaborate on the theoretical rationale that obesity-triggered low-grade inflammatory proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…In fact, neutrophils from obese rats shown decreased chemotactic migration to LPS compared to control animals. It is possible that an obesity-related neutrophil impairment contributes to the unexpected lower inflammation observed in Obese-ALI (8, 9). Levels of the anti-inflammatory cytokine IL-10 in lung tissue, as well as gene expression of IL-10 in monocytes, were both increased in Obese-ALI to Control-ALI animals; this may be attributed to increased M2 macrophage activation due to the increased total number of adipocytes (5052).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, neutrophils from obese rats shown decreased chemotactic migration to LPS compared to control animals. It is possible that an obesity-related neutrophil impairment contributes to the unexpected lower inflammation observed in Obese-ALI (8, 9). Levels of the anti-inflammatory cytokine IL-10 in lung tissue, as well as gene expression of IL-10 in monocytes, were both increased in Obese-ALI to Control-ALI animals; this may be attributed to increased M2 macrophage activation due to the increased total number of adipocytes (5052).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the pathophysiological mechanisms underlying the benefits of obesity in ARDS are poorly understood. It has been suggested that obesity is associated with continuous low-grade inflammation, which might protect the lungs from further insult, in the so-called “pre-conditioning cloud” (8). In experimental diet-induced obesity, neutrophil function including cytokine transcription, downstream signaling responses, and chemotaxis is impaired (911).…”
Section: Introductionmentioning
confidence: 99%
“…One pathophysiological mechanism postulated to explain the decreased mortality in critically ill patients with obesity is preconditioning, a chronic pro-inflammatory status in obesity that creates a protective environment, limiting the detrimental effects of a more aggressive second hit, such as ventilatorinduced lung injury or sepsis (3).…”
Section: To the Editormentioning
confidence: 99%
“…Indeed, preconditioning implies that a chronic proinflammatory status creates a protective environment, limiting the detrimental effects of a more aggressive second hit, such as ventilator-induced lung injury or sepsis. 45 A more simplistic approach postulated that the lower resuscitation fluid volume to body weight used in the obese patients confers them a survival advantage by applying a "restrictive fluid" strategy. 46 Nevertheless, these and other proposed mechanisms (summarized in ►Table 1) remain speculative at the moment 42 and deserve further investigation.…”
Section: Obesity As a Risk Factor For Ardsmentioning
confidence: 99%